Effect of Repeated Wetting-Drying-Freezing-Thawing Cycles on the Mechanic Properties and Pore Characteristics of Compacted Loess - Fei Wang; Guoyu Li; Wei Ma; Yanhu Mu; Zhiwei Zhou; Jun Zhang; Dun Chen; Jinshuai Zhao (Advances in Civil Engineering)
A series of laboratory experiments, including oedometer tests, direct shear tests, and mercury intrusion porosity (MIP) tests, were conducted to investigate the effects of repeated wetting-drying-freezing-thawing (WDFT) cycles on the mechanic behaviors and pore characteristics of compacted loess. The results of mechanical tests indicate that the WDFT weathering can cause significant deterioration of mechanical properties for compacted loess. As the number of treatment cycles increases, vertical compression strain and coefficient of collapsibility of the loess specimens increase while the cohesion decreases. The compacted and noncollapsible loess specimen exhibits collapse again after the 7 WDFT cycles. The results of MIP tests show that WDFT cycles have a main influence on the pores with a pore diameter of 1∼35 μm between the soil aggregates, and medium pore contents (10∼35 μm) increase significantly with the increasing number of WDFT cycles. By comparing compression and collapse characteristics of the loess specimens subjected to wetting-drying, freeze-thaw, and WDFT cycles, we found that the dry-wet action plays the dominant role in the deterioration of engineering properties of compacted loess during WDFT cycles.